Transformasi Sosial dalam Pengelolaan Sampah Perkotaan: Studi Partisipasi dan Perubahan Perilaku Masyarakat Kota Makassar - Vidia, Nur Vidiah Rachmadani; Andi Alimuddin Unde; Muh Iqbal Latief (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2025)
Urban waste management is often perceived as a technical issue related to fleets, tonnage, and facilities, when in fact it is a social phenomenon that reflects the relationship between policy, community behavior, and institutional structures. This paper aims to analyze the social dynamics of waste management in Makassar City by emphasizing the interaction between policy structures, social norms, and community participation. The study used a descriptive qualitative approach through in-depth interviews, focus group discussions, and participant observation at the Waste Bank, TPS3R, and Tamangapa Landfill. The results show that household participation in waste sorting remains low (42.1%), the Waste Bank's contribution to waste reduction is only 0.17%, and formal regulations have not fully changed community behavior. Analysis using Giddens' structuration theory confirms that formal policies do not automatically result in behavioral change without the internalization of environmental norms. Meanwhile, Ajzen's theory of planned behavior explains the weak community intention due to low social pressure and limited sorting facilities. From the perspective of Arnstein's Ladder of Participation, community participation remains at the level of tokenism, not yet reaching partnership or citizen control. The novelty of this research lies in its emphasis on integrating social and technical aspects in understanding waste management, while also offering an approach based on social justice and community empowerment. The implications of this research are the need for policies that not only increase technical facilities but also strengthen social capital, environmental education, and public participation as the foundation for sustainable waste management.